Photosynthetic characteristics of two Cylindrospermopsis raciborskii strains differing in their toxicity. Issue 2 (17th January 2014) - Pierangelini, Mattia; Stojkovic, Slobodanka; Orr, Philip T.; Beardall, John; Lindell, D.
<x xml:space="preserve">Abstract</x> We studied the growth and photosynthetic characteristics of a toxic (CS506) and a nontoxic strain (CS509) of the bloom‐forming cyanobacterium Cylindrospermopsis raciborskii grown under identical experimental conditions. When exposed to light‐saturating growth conditions (100 μmol photons · m−2 · s−1), values for maximal photosynthetic capacity (Pmax) and maximum quantum yield (Fv/Fm) indicated that both strains had an equal ability to process captured photons and deliver them to PSII reaction centers. However, CS506 grew faster than CS509. This was consistent with its higher light requirement for saturation of photosynthesis (Ik). Greater shade tolerance of CS509 was indicated by its higher ability to harvest light (α), lower photosynthetic light compensation point (Ic), and higher chlorophyll a to biovolume ratio. Strain‐specific differences were found in relation to non‐photochemical quenching, effective absorption cross‐sectional area of PSIIα‐centers (σPSIIα), and the antenna connectivity parameter of PSIIα (JconPSIIα). These findings highlighted differences in the transfer of excitation from phycobilisome/PSII to PSI, on the dependence on different pigments for light harvesting and on the functioning of the PSII reaction centers between the two strains. The results of this study showed that both performance and composition of the photosynthetic apparatus are different between these strains, though with only two strains examined we cannot attribute the performance of strain 506 to its ability to produce cylindrospermopsins. The emphasis on a strain‐specific light adaptation/acclimation is crucial to our understanding of how different light conditions (both quantity and quality) can trigger the occurrence of different C. raciborskii strains and control their competition and/or dominance in natural ecosystems.